Prevalensi diabetes melitus tipe 2 pada masa pandemi COVID-19 di praktik dokter keluarga Kota Manado - Husain, Anisa A.; Rombot, Dina Victoria; Porajow, Zwingly Christian Jefferson Gerard (UNIVERSITAS SAM RATULANGI, 2022)
Diabetes mellitus (DM) is a metabolic disorder characterized by high blood sugar levels. As the 6th leading cause of death in developing countries, type 2 DM (T2DM) accounts for 90% of all DM cases. Basic Health Research (Riskesdas) 2018 states prevalence of DM in Manado City was 4.51%. This study aims to determine the epidemiological data of T2DM during the COVID-19 pandemic in family doctor practices in Manado City, with the specific aim of knowing its prevalence and pattern of it. This study was a retrospective descriptive study with a cross-sectional study design. Data were from the medical record data of T2DM patients in family doctor practices in Manado City from June 2021 to May 2022. The results showed that the prevalence of T2DM in family doctor practices was 28.64%. Most patients with type 2 diabetes mellitus were female, and most T2DM patients were over 65 years old. Local health services can carry out counselling efforts to prevent DM disease. Keywords: type 2 diebetes mellitus, prevalence, incidence pattern, age, sex